2016
DOI: 10.1111/jfpp.12776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myrtle (Myrtus communisL.) Fruit Cold Storage Under Modified Atmosphere on Liqueur Quality

Abstract: Myrtle berries were stored for 30 days at 2C in air (control) or O 2 at 60 or 80% with the aim to extend the liqueur processing season. Oxygen treated berries had a lower pH and titratable acidity than control. No treatment effect was observed on weight loss and respiration rate. CIELAB coordinates demonstrated a darkening of the oxygen treated fruit. Hydro-alcoholic extracts (HAE) from berries stored for 30 days at 80% O 2 were less red colored than other treatments. After 10 and 20 days of storage, fruit hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Although the berries decoctions had been used to bathe newborns with reddened skin, and the decoctions of leaves and berries in sore washing, the most is used to produce the characteristic myrtle liqueur obtained by hydro-alcoholic infusion of the berries [ 4 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the berries decoctions had been used to bathe newborns with reddened skin, and the decoctions of leaves and berries in sore washing, the most is used to produce the characteristic myrtle liqueur obtained by hydro-alcoholic infusion of the berries [ 4 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to store berries in cold conditions during a defined period, or even freeze them, however, some studies have also concluded that these procedures are not free of undesirable effects, namely in the alteration of fruit composition and, therefore, in the liqueur quality [ 99 ]. According to Fadda et al [ 14 ], oxygen-enriched atmospheres have been successfully used to retain the quality of stored fruit and vegetables. For this reason, they proposed to evaluate the effect of different high oxygen treatments on physicochemical quality of myrtle berries and their corresponding hydro-alcoholic extracts used for the preparation of the liqueur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying the effects of cold storage of blueberries under an atmosphere modified for liquor quality, Fadda et al (Fadda et al, 2017) observed that since the first 10 days of storage, the colour of the blueberry changed from violet to dark red, that was one of the reasons for the decrease in L* values. Tuberoso et al 2008 Development, v. 9, n. 9, e884998227, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.8227 protein in its composition, and the free amino acids from the pulp can react with reducing sugars synthesizing melanoidins.…”
Section: Resultsmentioning
confidence: 99%
“…For the chromaticity coordinate a* there was an increase with the storage period, indicating a tendency to move away from green. Fadda et al (2017), in their study about the effects of cold storage of blueberries under atmosphere modified for liquor quality, observed that since the first 10 days of storage, the colour of the blueberry changed from violet to dark red, that was one of reasons for the decrease in b* and hue angle associated with an increase in redness (a*). Dias et al (2011), when studying the influence of temperature on the physical, physical-chemical and chemical changes of banana peel jelly cultivar Prata during storage, observed that at 75 days there was an increase in the red colour (a*), tending to reduce to the end of storage.…”
Section: Resultsmentioning
confidence: 99%